2014
DOI: 10.1137/120888776
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Toeplitz Regularized Least Squares Computation for Image Restoration

Abstract: The main aim of this paper is to develop a fast algorithm for solving weighted Toeplitz regularized least squares problems arising from image restoration. Based on augmented system formulation, we develop new Hermitian and skew-Hermitian splitting (HSS) preconditioners for solving such linear systems. The advantage of the proposed preconditioner is that the blurring matrix, weighting matrix, and regularization matrix can be decoupled such that the resulting preconditioner is not expensive to use. We show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Matrices have important applications in pure and applied mathematics [3,24,29]. Many scholars study their properties as well as the representation of their inverse formula.…”
Section: Introductionmentioning
confidence: 99%
“…Matrices have important applications in pure and applied mathematics [3,24,29]. Many scholars study their properties as well as the representation of their inverse formula.…”
Section: Introductionmentioning
confidence: 99%
“…Toeplitz matrix has become a satisfactory tool in restoration of signals and images [6,24,25]. Toeplitz inversion formulae involving circulant matrices have also been presented in [1,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Toeplitz matrix has become a satisfactory tool in restoration of signals and images [5,26,27]. In [4,7], the authors introduced a generalization of Toeplitz matrices, called conjugate-Toeplitz (CT) matrices, and showed that certain properties of Toeplitz matrices could be extended to CT matrices.…”
Section: Introductionmentioning
confidence: 99%